Introgressão de alelos de arachis selvagens visando ao aumento da tolerância á seca no amendoim cultivado - Dutra, Wellison Filgueiras (2019)
Drought is a meteorological phenomenon that causes significant losses in agriculture, especially in arid and semiarid regions, such as the Brazilian Northeast. The use of tolerant cultivars is among the main strategies for coexist with drought and uplift the relevant species cultivation. In this context, peanut is an oilseed of great socioeconomic importance for the semiarid region, predominantly cultivated by family-based farmers. Because it is one of the few tetraploid species of the genus Arachis, cultivated peanut are reproductively isolated from wild relatives, most of them diploid. However, even with chromosome barriers, the wild species use is seen as an excellent alternative to increase the genetic variability of cultivated peanuts and to develop new cultivars adapted to the semiarid climate. Currently, several alotetraploids have been obtained by Embrapa multidisciplinary team, which are being evaluated for drought tolerance. In the present study, selection and validation procedures were performed on a population of peanut allotetraploids {BR 1 x [BR 1 x (A. batizocoi K9484 x A. duranensis SeSn 2848)4x]} based on drought tolerance, using physiological and agronomic descriptors (Chapter I). Then, peanut alotetraploides were evaluated in greenhouse and field, focusing on molecular, biochemical and agronomic characteristics, in order to identify and select plants with better ability to adjust to water stress (Chapter II). Initially sixty-four alotetraploids were grown in a greenhouse in Campina Grande-PB during the dry season. After flowering, irrigation was suspended for 15 days and resumed after this period. Three genotypes were used as controls: BR1, Senegal 55-437 (tolerant to water stress) and LViPE-06 (sensitive to water stress). On the last day of stress, gas exchange and non-photochemical quenching (NPQ) were measured in all plants. These data were used in the selection of alotetraploids with drought tolerance, along with agronomic descriptors related to production and precocity. The selected plants were cultivated in two environments (Lagoa Seca and Campina Grande) in order to validate the drought tolerance. Cultivation was carried out in the rainy season, and agronomic descriptors related to precocity, production and water use efficiency were evaluated. Gene expression, superoxide dismutase type’s activity (SOD) and proline content were also evaluated in selected plants. Based on the tests performed, several alotetraploids have drought tolerance, with similar or higher characteristics than those observed in the cultivar currently cultivated in the Northeast of Brazil (BR 1). Alotetraploids have expression differentiated levels of SOD types and the proline precursor, and there is a relationship between the transcripts production and the metabolites synthesis subsequent. The 53 P4 and 96 P9 lines were more productive and efficient in the water use, denoting to be promising for the cultivation in semiarid conditions. The adoption of these materials represents an opportunity to broaden the genetic base of future cultivars, as well as to subsidize the wild genetic resources use in breeding programs facing semiarid.